2016
DOI: 10.1111/icad.12209
|View full text |Cite
|
Sign up to set email alerts
|

Watch your step: insect mortality on hiking trails

Abstract: Hiking may have a negative effect on vertebrates, but the impact on insects is unknown. Large‐scale hiking may lead to habitat degradation, the introduction of alien species and the killing of insects occurring in places visited by people. The aim of this study was to determine the influence of hiking on the mortality of insects. Randomly selected hiking trails in the western Carpathians (southern Poland) were surveyed and dead insects lying on the trails were collected. To compare the composition of ground‐dw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Floral resources can be considered as a limiting factor for populations of bees (Roulston & Goodell, 2011), syrphid flies (Hegland & Boeke, 2006;Meyer, Jauker, & Steffan-Dewenter, 2009), and Lepidoptera (Ockinger & smith, 2006). The present study showed that the disturbance resulting from the hiking trail had a negative impact on different species of flower visitors and their associated floral resources in Wadi Telah, which is clear from the spatial distribution of species richness of flower visitors and their associated floral resources among different distances from the hiking trail in W. Telah, which is concurred with the view of Ciach, Maślanka, Krzus, and WOJAS (2017) who reported that species richness and abundance of insect pollinators decreases with increased hiking trail disturbances by a human. Similarly, Gray and Jongepier (2012) showed a decrease in insect species diversity with an increase in the human disturbance, when studying the relationship between the level of human disturbance and the diversity of arthropod communities in Kirindy Forest, Western Madagascar.…”
Section: Discussionsupporting
confidence: 88%
“…Floral resources can be considered as a limiting factor for populations of bees (Roulston & Goodell, 2011), syrphid flies (Hegland & Boeke, 2006;Meyer, Jauker, & Steffan-Dewenter, 2009), and Lepidoptera (Ockinger & smith, 2006). The present study showed that the disturbance resulting from the hiking trail had a negative impact on different species of flower visitors and their associated floral resources in Wadi Telah, which is clear from the spatial distribution of species richness of flower visitors and their associated floral resources among different distances from the hiking trail in W. Telah, which is concurred with the view of Ciach, Maślanka, Krzus, and WOJAS (2017) who reported that species richness and abundance of insect pollinators decreases with increased hiking trail disturbances by a human. Similarly, Gray and Jongepier (2012) showed a decrease in insect species diversity with an increase in the human disturbance, when studying the relationship between the level of human disturbance and the diversity of arthropod communities in Kirindy Forest, Western Madagascar.…”
Section: Discussionsupporting
confidence: 88%
“…Meanwhile, species-specific fruit production responses to disturbance could be related to the effect that disturbance might have on pollinators. For example, insects, which might be negatively affected by human trampling [47], could reduce their pollination services for insect-pollinated species near trails. While it is unclear how negative effects on growth may scale up to influence population persistence in perennial species, decreases in reproduction are more closely tied to plant fitness.…”
Section: Species-specific Responsesmentioning
confidence: 99%
“…Similar results were obtained by Gray and Jongepier (2012) who reported a decrease in arthropod species diversity with an increase in human disturbance at Kirindy Forest, Western Madagascar. Hiking trails usage had negative impacts on insect populations, where hiking trail acts as a barrier to dispersal of non-flying species (Mader, 1984;Ciach et al, 2017). Contrary to that, Kwon (2015) found that high ant abundance were observed towards the trail and less population tended to be located further from the trails.…”
Section: Discussionmentioning
confidence: 94%